Small‐Sized CuS Nanoparticles/N, S Co‐Doped rGO Composites as the Anode Materials for High‐Performance Lithium‐Ion Batteries. Issue 6 (17th February 2019) - Ding, Xueda; Lei, Song; Du, Chengfeng; Xie, Zailai; Li, Jianrong; Huang, Xiaoying
Abstract: In this work, small‐sized CuS nanoparticles/N, S co‐doped rGO composites (CuS@N/S‐G‐C n ) are synthesized by a facile route with the metal‐containing ionic liquids (MILs) [C n MMim]2 [CuCl4 ] ( n is 6, 8, 10 representing the number of C atoms in the alkyl chain of imidazolium cation) as the precursors. In the composites, the CuS nanoparticles with small size of sub‐20 nm are homogeneously dispersed in nitrogen and sulfur co‐doped reduced graphene oxide (rGO). The highly dispersed nanosized CuS are embedded on excellent conductive doped rGO substrates to supply not only large quantity of accessible active sites for lithium‐ion insertion but also short diffusion length for lithium ions, while the N and S co‐doping in rGO can efficiently restrain the polysulfides dissolution and circumvent the volume expansion/contraction associated with lithium insertion/extraction during charge–discharge processes. Bestowed by these advantages, the CuS@N/S‐G‐C n composites exhibit enhanced electrochemical performance for lithium storage. Especially, when [C6 MMim]2 [CuCl4 ] is chosen as the precursor, the obtained electrode material CuS@N/S‐G‐C6 delivers a reversible capacity as high as 603.5 mAh g −1 at 200 mA g −1 after 300 cycles and 530 mAh g −1 at 2 A g −1 after 1000 cycles. Abstract : Small‐sized CuS nanoparticles/N, S co‐doped rGO composites with facile synthesis and high electrochemical performance show significance in practical application toward lithium‐ion batteries.